2021
DOI: 10.1021/acsami.1c04125
|View full text |Cite
|
Sign up to set email alerts
|

Selective Enhancement in Phonon Scattering Leads to a High Thermoelectric Figure-of-Merit in Graphene Oxide-Encapsulated ZnO Nanocomposites

Abstract: ZnO is a promising candidate as an environment friendly thermoelectric (TE) material. However, the poor TE figure of merit (zT) needs to be addressed to achieve significant TE efficiency for commercial applications. Here we demonstrate that selective enhancement in phonon scattering leads to increase in zT of RGO encapsulated Al-doped ZnO core shell nanohybrids, synthesized via a facile and scalable method. The incorporation of 1 at% Al with 1.5 wt% RGO into ZnO (AGZO) has been found to show significant enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…The specific heat capacity used for the TDTR simulation was measured using differential scanning calorimetry (DSC, DSC8500, PerkinElmer) (Supporting Information, Figure S3). The in-plane κ of the films was extracted according to the following equation as previously reported. , where φ, κ obsd , κ // and κ ⊥ are the inclination angle of the layers relative to the perpendicular of the film surface, observed thermal conductivity, in-plane κ, and cross-plane κ, respectively (Supporting Information, Figure S4). In this study, φ = 35°, which was proven by scanning transmission electron microscopy (STEM) observations in our previous study …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific heat capacity used for the TDTR simulation was measured using differential scanning calorimetry (DSC, DSC8500, PerkinElmer) (Supporting Information, Figure S3). The in-plane κ of the films was extracted according to the following equation as previously reported. , where φ, κ obsd , κ // and κ ⊥ are the inclination angle of the layers relative to the perpendicular of the film surface, observed thermal conductivity, in-plane κ, and cross-plane κ, respectively (Supporting Information, Figure S4). In this study, φ = 35°, which was proven by scanning transmission electron microscopy (STEM) observations in our previous study …”
Section: Methodsmentioning
confidence: 99%
“…Since most metal oxides show good chemical and thermal stability in air as well as a harmless nature compared to chalcogenide-based state-of-the-art thermoelectric materials, oxide-based thermoelectric materials that show a high ZT are promising. , Several high- ZT thermoelectric oxides have been reported thus far; Fujita et al reported that the Na x CoO 2 single crystal exhibited a ZT of ∼1.2 at 800 K. Acharya et al . reported that Nb-doped SrTiO 3 with natural graphite exhibited a ZT of ∼1.42 at 1050 K. Biswas et al reported that graphene oxide-encapsulated ZnO nanocomposites exhibited a ZT of ∼0.52 at 1100 K. However, the reliability is considerably low due to a lack of careful observation of their stability at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the number of scattering centers leads to a rapid increase in electrical resistivity. Biswas et al reported that the thermal conductivity of Al-doped ZnO quantum dots is reduced due to the selective phonon scattering by point defects and interfaces, and thereby an enhanced PF value [ 41 ]. Further, the lattice thermal conductivity of this composite could be dominated by grain boundaries and hence phonon–phonon scatterings.…”
Section: Resultsmentioning
confidence: 99%
“…For TE applications, ZnO doped with cations, such as Al 3+ , , Cd 2+ , Ni 2+ , and Ga 3+ , and those co-doped with other cations have been studied. ,,, However, due to the low solubility of solute ions in ZnO and its relatively high κ values (e.g., κ ∼ 8 W/(m·K) at 900 °C, its TE performance is rather limited. The low solubility limit of dopants in ZnO leads to the formation of second phases, which restricts its TE performance.…”
Section: Introductionmentioning
confidence: 99%